Preparation method of three-dimensional multi-channel gas sensor for H2S gas detection

The three-dimensional multi-channel Ag@WO3 material was synthesized by hydrothermal method, and the sensitization of Ag was used to improve the response performance to H2S gas, and the solution was to the low sensitivity of Ag modified WO3 sensing materials in the prior art when detecting H2S gas at room temperature. , the problem of narrow detection range and poor selectivity has achieved high sensitivity, low detection lower limit and high selectivity H2S gas detection.

CN119461485AActive Publication Date: 2025-02-18TIANJIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411635130.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing Ag modified WO3 sensing materials have low sensitivity, narrow detection range, poor selectivity, and high operating temperature when detecting H2S gas at room temperature.

Method used

The three-dimensional multi-channel Ag@WO3 material was synthesized by hydrothermal method, and the electronic and chemical sensitization of Ag and the vulcanization reaction between Ag and H2S were used to significantly improve the gas-sensitive response performance of the sensitive layer material to H2S gas.

Benefits of technology

It has achieved an ultra-high response value for 10ppm H2S gas at room temperature of 25°C, with a lower detection limit as low as 10ppb, and a response time of only 7s, with high selectivity and good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461485A_ABST
    Figure CN119461485A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a three-dimensional multi-channel gas sensor for H2S gas detection, an Ag-doped WO3 material is prepared by a hydrothermal method, and the prepared Ag-coated WO3 is in a three-dimensional nanoflower shape self-assembled by nanosheets. According to the three-dimensional hierarchical structure, the high sensitivity of the sensitive layer to H2S gas can be promoted by the electronic and chemical sensitization effects of noble metal Ag and the sulfuration reaction of Ag and H2S, rapid response, high-sensitivity and high-selectivity detection of H2S gas can be realized at room temperature, and the practical application in atmospheric pollution detection is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas sensors, and in particular relates to a method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection. Background Art

[0002] Hydrogen sulfide is a flammable and explosive acidic gas with the smell of rotten eggs. A large amount of H2S is produced in daily human activities, such as the production of domestic waste, automobile exhaust emissions, coal coking and power plants, etc. [1] When the H2S gas in the air is higher than a certain value, it will cause certain harm to the human body, including respiratory infections, pulmonary edema, headaches, hypotension, dyspnea, and even death. [2,3] For safety reasons, the American Conference of Governmental Industrial Hygienists has set the threshold of H2S gas at 10ppm and the exposure time for humans should not exceed 8h. [4] The acceptable environmental limit for H2S (recommended by the US Toxic Air Pollutants Scientific Advisory Committee) is between 20-100 ppb [5] In addition, H2S can also be used as a biomarker for the diagnosis of medical diseases such as bad breath, asthma and chronic obstructive pulmonary disease. [6] Therefore, the development of high-performance H2S gas sensors is very necessary to ensure human life safety, protect the living environment and promote the development of smart medicine.

[0003] A gas sensor is a device that converts chemical signals into electrical signals. The key core part is the selection of sensitive layer materials. [7] Metal oxide semiconductor (MOS) gas sensors have become the mainstream research material due to their advantages such as easy manufacturing, low cost and high sensitivity. The materials currently used for H2S gas detection mainly include WO3 [8] 、SnO2 [9,10] 、TiO

[11] 、ZnO

[12] 、Co3O4

[13] 、In2O3

[14] wait.

[0004] Among many MOSs, WO3, as a typical n-type semiconductor, has a bandgap of 2.4-2.8eV. Its structure is similar to that of perovskite, with abundant oxygen vacancies and active adsorption sites, which indicates that it has great application prospects in H2S gas detection.

[15] For example, Li et al.

[16] A simple topological transformation strategy was used to synthesize porous two-dimensional WO3 nanosheets with a response value of 35.55 to 2000 ppb H2S at 160 °C. Zhu et al.

[17] The prepared WO3 film has excellent gas sensitivity, repeatability and stability to H2S at 250℃, with the response value to 10ppm H2S being 40.1.

[0005] Although pure WO3 has good gas sensing performance for H2S, it still has disadvantages such as high operating temperature, poor response value and selectivity. Therefore, it needs to be modified to improve the gas sensing performance of the sensor to meet the needs of practical applications.

[18] .

[0006] It is reported that various precious metal modified WO3 materials have been applied to H2S gas sensors, mainly focusing on Pd [19,20] , Pt [21-27] 、Au[ 28-30] , a few papers reported that Ag modified WO3 [31-33] Ahmad et al.

[31] The synthesized silver-doped tungsten oxide nanoparticle (Ag / WO3) material is capable of detecting H2S gas as low as 0.25 ppm at room temperature. Gui et al.

[32] Ag / WO3 / rGO bulk sensor was prepared by microwave-assisted gas-liquid interface method, and the response value to 100 ppm H2S at 150°C was 204.5, which is about 7 times that of WO3 / rGO. Jang et al.

[33] Hollow bimetallic Pt-Ag nanoparticles (NPs) with a size below 10 nm were prepared and sensitized on multilayer SnO-WO3 heterojunction nanofibers (HNFs). The bimetallic catalyst enabled excellent H2S sensitivity for halitosis breath detection.

[0007] It can be seen that the strategy of noble metal modified WO3 gas sensor can fully improve the gas-sensing performance of H2S detection, but the existing Ag modified WO3 sensing materials usually have a high working temperature for detecting H2S gas, or have low sensitivity, narrow detection range and poor selectivity at room temperature.

[0008] Therefore, it is necessary to establish a simple, efficient, accurate and reliable sensor preparation method, especially to achieve the detection of H2S gas as low as ppb level at room temperature, and the sensor has high response value, wide detection range, low detection limit, high selectivity and good stability.

[0009] References

[0010] [1]J.Wang,Y.Ren,H.Liu,Z.Li,X.Liu,Y.Deng,X.Fang,Ultrathin 2DNbWO6Perovskite Semiconductor Based Gas Sensors with Ultrahigh Selectivityunder Low Working Temperature,Adv Mater,34(2022)e2104958.

[0011] [2]R.T.Ghahrizjani,R.M.Maleki,M.Ghafarkani,A.Esmaeili,M.Ameri,E.Mohajerani,N.Safari,Y.Dou,S.X.Dou,Highly sensitive H2S gas sensorcontaining simultaneously UV treated and self-heated Ag-SnO2 nanoparticles,Sensors and Actuators B:Chemical,391(2023)134045.

[0012] [3]X.Zhang,Q.Wei,H.Zhao,F.Wei,T.Li,Porous-Pt-CuO-drivenelectrochemical biosensor for tracking of endogenous H2S biomessengermolecules,Ceramics International,49(2023)16849-16856.

[0013] [4]J.Nii OkaiAmu-Darko,S.Hussain,X.Zhang,A.M.Karami,M.Sufyan Javed,K.Yusuf,R.K.Manavalan,M.Wang,G.Qiao,G.Liu,Enhanced H2S gas sensing utilizingUV-assisted In2O3@ZnO nanosheets,Ceramics International,50(2024)38242-38252.

[0014] [5]M.Kaur,N.Jain,K.Sharma,S.Bhattacharya,M.Roy,A.K.Tyagi,S.K.Gupta,J.V.Yakhmi,Room-temperature H2S gas sensing at ppb level by single crystalIn2O3whiskers,Sensors andActuators B:Chemical,133(2008)456-461.

[0015] [6]N.Y.Kim,M.H.Lee,Self-correcting ratiometric fluorescence assay forH2S detection in live cells and releasing agents,Sensors and Actuators B:Chemical,422(2025)136567.

[0016] [7]Y.Wang,J.Li,D.Xiao,D.Zhang,Y.Liu,M.Sun,S.Chen,M.Sun,Progress infunctionalized WO3-based gas sensors for selective H2S and NH3:Areview,Ceramics International,50(2024)40631-40665.

[0017] [8]B.Yang,D.T.H.To,E.Resendiz Mendoza,N.V.Myung,Achieving One PartPer Billion Hydrogen Sulfide(H2S)Level Detection through OptimizingComposition and Crystallinity of Gold-Decorated Tungsten Trioxide(Au-WO3)Nanofibers,ACS Sens,9(2024)292-304.

[0018] [9]A.Kumar,A.K.Shringi,M.Kumar,RF sputtered CuO anchored SnO2 for H2Sgas sensor,Sensors andActuators B:Chemical,370(2022)132417.

[0019]

[10] S.Ruksana,A.Kumar,S.Lakshmy,K.R.Kishore,C.S.Sharma,M.Kumar,B.Chakraborty,Highly Efficient CuO-Anchored SnO2 Nanofiber for Low-Concentration H2S Gas Sensors,ACS Applied Engineering Materials,2(2024)431-442.

[0020]

[11] W.Wu,J.Long,Y.Guo,X.Zu,S.Li,X.Xiang,P-CuO / n-TiO2 heterojunctionnanostructure-based surface acoustic wave sensor with strong electric loadingeffect for highly sensitive H2S gas sensing,Sensors and Actuators B:Chemical,394(2023)134380.

[0021]

[12] D.Xiao,Y.Wang,D.Zhang,Y.Liu,H.Wang,Y.Li,H.Wei,S.Wang,M.Sun,M.Sun,CuO / ZnO hollow nanocages derived from metal-organic frameworks for ultra-highand rapid response H2S gas sensor,Ceramics International,50(2024)15767-15779.

[0022]

[13] A.N.Begi,S.Hussain,J.N.O.Amu-Darko,S.Shah,W.Junhao,X.Zhang,K.Yusuf,R.K.Manavalan,G.Qiao,G.Liu,Low-concentration H2S gas sensors based onMOF-derived Co3O4 nanomaterials,Sensors andActuators A:Physical,378(2024)115776.

[0023]

[14] J.N.Okai Amu-Darko,S.Hussain,X.Zhang,A.A.Alothman,M.Ouladsmane,M.T.Nazir,G.Qiao,G.Liu,Metal-organic frameworks-derived In2O3 / ZnO poroushollow nanocages for highly sensitive H2S gas sensor,Chemosphere,314(2023)137670.

[0024]

[15] M.Guo,N.Luo,Y.Chen,Y.Fan,X.Wang,J.Xu,Fast-response MEMS xylenegas sensor based on CuO / WO3 hierarchical structure,J Hazard Mater,429(2022)127471.

[0025]

[16] X.Li,H.Yang,X.Wang,Z.Qin,X.Hu,X.Wang,C.Xie,D.Zeng,Exposed edgesofporous ultrathin WO3 nanosheets determined High-performance sensing forhydrogen sulfide,Applied Surface Science,571(2022)151327.

[0026]

[17] C.Zhu,T.Lv,H.Yang,X.Li,X.Wang,X.Guo,C.Xie,D.Zeng,Influence ofmagnetron sputtering process on the stability of WO3 thin film gas sensor,Materials Today Communications,34(2023)105116.

[0027]

[18] L.Y.Zhu,L.X.Ou,L.W.Mao,X.Y.Wu,Y.P.Liu,H.L.Lu,Advances in NobleMetal-Decorated Metal Oxide Nanomaterials for Chemiresistive Gas Sensors:Overview,Nano-Micro Letters,15(2023).

[0028]

[19] Y.Guo,B.Liu,Z.Duan,Z.Yuan,Y.Jiang,H.Tai,Batch fabrication of H2Ssensors based on evaporated Pd / WO3 film with ppb-level detection limit,Materials Chemistry and Physics,302(2023)127768.

[0029]

[20] C.Wang,Y.Zhang,X.Sun,Y.Sun,F.Liu,X.Yan,C.Wang,P.Sun,G.Lu,Preparation of Pd / PdO loaded WO3 microspheres for H2S detection,Sensors andActuators B:Chemical,321(2020)128629.

[0030]

[21] Y.Zhang,J.Chang,Y.Wang,Mechanism analysis of PtPd-decoratedhexagonal WO3 nanorods for H2S sensing application with ppt-level detectionlimit,Journal of Alloys and Compounds,892(2022)162133.

[0031]

[22] X.Yao,J.Zhao,J.Liu,F.Wang,L.Wu,F.Meng,D.Zhang,R.Wang,J.Ahmed,K.Ojha,H2S sensing material Pt-WO3 nanorods with excellent comprehensiveperformance,Journal ofAlloys and Compounds,900(2022)163398.

[0032]

[23] N.Van Toan,C.M.Hung,N.D.Hoa,N.Van Duy,D.Thi Thanh Le,N.Thi ThuHoa,N.N.Viet,P.H.Phuoc,N.Van Hieu,Enhanced NH3 and H2 gas sensing with H2S gasinterference using multilayer SnO2 / Pt / WO3 nanofilms,Journal of HazardousMaterials,412(2021)125181.

[0033]

[24] H.Shin,D.H.Kim,W.Jung,J.S.Jang,Y.H.Kim,Y.Lee,K.Chang,J.Lee,J.Park,K.Namkoong,I.D.Kim,Surface Activity-Tuned Metal Oxide Chemiresistor:Toward Direct and Quantitative Halitosis Diagnosis,ACS Nano,15(2021)14207-14217.

[0034]

[25] M.H.Kim,J.S.Jang,W.T.Koo,S.J.Choi,S.J.Kim,D.H.Kim,I.D.Kim,Bimodally Porous WO3 Microbelts Functionalized with Pt Catalysts forSelective H2S Sensors,ACS Applied Materials&Interfaces,10(2018)20643-20651.

[0035]

[26] D.H.Kim,J.S.Jang,W.T.Koo,S.J.Choi,H.J.Cho,M.H.Kim,S.J.Kim,I.D.Kim,Bioinspired Cocatalysts Decorated WO3 Nanotube Toward UnparalleledHydrogen Sulfide Chemiresistor,ACS Sensors,3(2018)1164-1173.

[0036]

[27] S.J.Choi,K.H.Ku,B.J.Kim,I.D.Kim,Novel Templating Route Using PtInfiltrated Block Copolymer Microparticles for Catalytic Pt FunctionalizedMacroporous WO3 Nanofibers and Its Application in Breath Pattern Recognition,ACS Sensors,1(2016)1124-1131.

[0037]

[28] M.Punginsang,D.Zappa,E.Comini,A.Wisitsoraat,G.Sberveglieri,A.Ponzoni,C.Liewhiran,Selective H2S gas sensors based on ohmic hetero-interface of Au-functionalizedWO3 nanowires,Applied Surface Science,571(2022)151262.

[0038]

[29] J.Lee,Y.Jung,S.-H.Sung,G.Lee,J.Kim,J.Seong,Y.-S.Shim,S.C.Jun,S.Jeon,High-performance gas sensor array for indoor air quality monitoring:the role of Au nanoparticles on WO3,SnO2,and NiO-based gas sensors,Journal ofMaterials ChemistryA,9(2021)1159-1167.

[0039]

[30] S.Yang,J.Sun,L.Xu,Q.Zhou,X.Chen,S.Zhu,B.Dong,G.Lu,H.Song,Au@ZnOfunctionalized three–dimensional macroporous WO3:A application of selectiveH2S gas sensor for exhaled breath biomarker detection,Sensors and ActuatorsB:Chemical,324(2020)128725.

[0040]

[31] A.Al-Sarraj,R.Al Soubaihi,K.M.Saoud,A.I.Ayesh,A.Bermak,Sub-ppm oftoxic gases detection onAg-doped WO3 nanosensor,Emergent Materials,(2024).

[0041]

[32] Y.Gui,J.Wu,K.Tian,H.Guo,X.Qin,X.Qin,X.Guo,C.Fang,P.Liu,Ultraviolet-Induced Gas Sensing Performance of Ag / WO3 / rGO Nanocomposites forH2S Gas Sensors,ACSApplied Electronic Materials,5(2023)3625-3633.

[0042]

[33] JSJang, SJChoi, WTKoo, SJKim, JYCheong, IDKim, ElaborateManipulation for Sub-10nm Hollow Catalyst Sensitized Heterogeneous OxideNanofibers for Room Temperature Chemical Sensors, ACS Applied Materials & Interfaces, 9 (2017) 24821-24829. Summary of the invention

[0043] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection. A simple hydrothermal method is used to synthesize a three-dimensional nanoflower-like Ag@WO3 material with multiple gas dispersion channels. The three-dimensional hierarchical structure, the electronic and chemical sensitization of the precious metal Ag, and the sulfurization reaction of Ag and H2S will significantly improve the gas-sensitive response performance of the Ag@WO3 sensitive layer material to H2S gas.

[0044] The present invention solves the technical problem by the following technical solutions:

[0045] A method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection, the method comprising the following steps:

[0046] S1. Measure a certain amount of ethanol solution and pour it into a 100 mL beaker. Add a certain amount of WCl6 into the beaker and stir evenly with a magnetic stirrer to obtain a mixed solution A.

[0047] S2, adding silver nitrate AgNO3 to the mixed solution A, stirring evenly with a magnetic stirrer to obtain a mixed solution B;

[0048] S3, add diammonium hydrogen citrate C6H 14 O7N2, and continuously stirred with a magnetic stirrer to fully mix the mixture to obtain a precursor solution;

[0049] S4, transferring the precursor solution into a 50 ml polytetrafluoroethylene reaction container and placing it in an oven for hydrothermal reaction;

[0050] S5, after the reaction is completed and cooled naturally, centrifugation and washing with deionized water and anhydrous ethanol are performed to obtain a precipitate C;

[0051] S6. Dry the precipitate C in a constant temperature vacuum drying oven for 6 to 10 hours, and then place it in a muffle furnace for calcination to obtain light yellow Ag-WO3 nanoflower powder.

[0052] Moreover, the magnetic stirring time of S1, S2 and S3 is 25 to 35 minutes.

[0053] Moreover, the oven temperature of S4 is 90-110° C., and the hydrothermal reaction time is 23-25 ​​h.

[0054] Moreover, the centrifugal speed of S5 is 2000-4000 r / min, the deionized water is centrifuged and washed 2-4 times, and the anhydrous ethanol is centrifuged and washed 2-4 times.

[0055] Moreover, the temperature of the constant temperature vacuum drying oven of S6 is 50-70°C, and the vacuum degree is maintained at 700-800Pa.

[0056] Moreover, the muffle furnace calcination heating rate of S6 is 2°C / min, and the calcination time at 440-460°C is 110-130min.

[0057] The positive effects that the present invention can produce are:

[0058] 1. The present invention utilizes a solvothermal method to synthesize a three-dimensional nano-flower-shaped Ag-doped WO3 sensitive layer with multiple gas dispersion channels without adding any template agent, in line with the "green chemistry development concept", reduces the preparation cost, and can achieve large-scale production.

[0059] 2. The present invention combines the preparation technology of Ag-doped WO3 nanomaterials with modern sensing technology to overcome the shortcomings of the prior art. In terms of detecting H2S gas, the doping of Ag significantly improves the reliability of the sensor, including high sensitivity and high selectivity.

[0060] 3. The Ag@WO3 sensor of the present invention can have an ultra-high response value (Ra / Rg=11420) to 10ppm H2S gas at room temperature 25°C, which is about 941 times that of pure WO3. It can continuously detect 1-50-1ppm H2S gas, with a detection limit as low as 10ppb and a response time of only 7s. It can cope with complex test environments and has strong engineering practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 a, b are XRD patterns and Fourier transform infrared spectra (FT-IR) of WO3, Ag@WO3-5, Ag@WO3-7, Ag@WO3-9 and Ag@WO3-11 sensors; Figure 1 c, d are Raman spectra of WO3, Ag@WO3-5, Ag@WO3-7, Ag@WO3-9 and Ag@WO3-11 sensors; Figure 1e)~g) are UPS spectra and high-resolution UPS spectra of WO3 and Ag@WO3-7 sensors;

[0062] Figure 2 a is the ultraviolet diffuse reflectance spectrum (UV-Vis) of WO3 and Ag@WO3-7 sensors; Figure 2 b is the Tauc plot of WO3 and Ag@WO3-7 sensors; Figure 2 c is the full XPS spectrum of WO3 and Ag@WO3 sensors. Figure 2 d~f are the fine spectra of W 4f, Ag 3d and O1s, respectively;

[0063] Figure 3 a~e are SEM images of WO3, Ag@WO3-5, Ag@WO3-7, Ag@WO3-9, and Ag@WO3-11, respectively; Figure 3 f~h are EDS element mappings of W, O, and Ag elements of Ag@WO3-7;

[0064] Figure 4 a, b are TEM and HRTEM images of WO3; Figure 4 c, d are TEM and HRTEM images of Ag@WO3-7;

[0065] Figure 5 a is the response diagram of WO3 to 10ppm H2S gas at different working temperatures; Figure 5 b is the response diagram of Ag@WO3-7-11 to 10ppm H2S gas at different working temperatures; Figure 5 c is the resistance curve of the sensor in air at different working temperatures; Figure 5 d is the response recovery curve; Figure 5 e is the continuous response curve diagram of 5 trials; Figure 5 f is the resistance curve of WO3 sensor in air at different working temperatures;

[0066] Figure 6 a~e are the response / recovery curves of sensors based on WO3, Ag@WO3-5, Ag@WO3-7, Ag@WO3-9, and Ag@WO3-11 to 10 ppm H2S gas at working temperature (40 and 25 °C), respectively; Figure 6 f is the response time and response value bar graph of all sensors;

[0067] Figure 7a~e are the continuous dynamic sensing characteristics of sensors Ag@WO3-5, Ag@WO3-7, Ag@WO3-, Ag@WO3-11, and Ag@WO3 to 1-50-1ppm H2S gas at 25°C, the response curves of the lower detection limit to H2S gas concentration, and the linear fitting data curve of the Ag@WO3-7 sensor; Figure 7 f is the statistical response diagram of Ag@WO3-7 at 25°C when the H2S concentration is 0.01-1ppm; (3 consecutive test curves when the H2S concentration is 10ppb);

[0068] Figure 8 a, b are the continuous cycle detection curve and response value curve of WO3 sensor to 1-30-1ppm H2S at 40℃ respectively;

[0069] Fig. 9 a is the selective response diagram of WO3 (40℃) and Ag@WO3-7 (25℃) sensors to different target gases; Fig. 9 b is the response diagram of Ag@WO3-7 sensor to 10ppm H2S at different relative humidity; Fig. 9 c is a bar graph of humidity response; Fig. 9 d is the graph of Ag@WO3-7 sensor tested with 10ppm H2S for 10 consecutive cycles at 25℃; Fig. 9 d is the long-term stability curve of Ag@WO3-7 sensor to 10 ppm H2S at 25°C;

[0070] Fig.10 a~c are the responses of Ag@WO3-5, Ag@WO3-9, and Ag@WO3-11 sensors to 10 ppm H2S at room temperature and different relative humidity, respectively; Fig.10 d is the response value curve at different humidity levels;

[0071] Fig.11 Schematic diagram of H2S gas sensing mechanism on Ag@WO3 sensor at room temperature;

[0072] Fig.12 a is the fine spectrum of O1s of Ag@WO3-7 sensor in air; Fig.12 b is the fine spectrum of O1s of Ag@WO3-7 sensor after sulfurization. DETAILED DESCRIPTION

[0073] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0074] Example 1

[0075] The present invention relates to a method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection, the innovation of which lies in the steps of the method comprising:

[0076] (1) Pour 20-40 mL of ethanol into a 100 mL beaker. Then add 1.30-1.34 g of WCl6 and stir with a magnetic stirrer;

[0077] (2) then adding 0-0.011 g of silver nitrate (AgNO3) and stirring with a magnetic stirrer;

[0078] (3) Then, add 0.5-0.6 g of diammonium hydrogen citrate (C6H 14 O7N2), stirring continuously with a magnetic stirrer to fully mix, to obtain a precursor solution;

[0079] (4) transferring the precursor solution into a 50 mL polytetrafluoroethylene reaction container and placing it in an oven for hydrothermal reaction;

[0080] (5) After cooling, the obtained precipitate A is washed by centrifugation with deionized water and anhydrous ethanol;

[0081] (6) Dry in a constant temperature vacuum drying oven for 6-10 hours,

[0082] (7) Then, calcination is carried out in a muffle furnace to finally obtain light yellow Ag-WO3 nanoflower powder.

[0083] Example 2

[0084] The present invention relates to a method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection, the innovation of which lies in the steps of the method comprising:

[0085] (1) Pour 30 mL of ethanol into a 100 mL beaker. Then add 1.32 g of WCl6 and stir with a magnetic stirrer for 30 min to allow it to fully dissolve in the solution.

[0086] (2) Then, add 0.007 g of silver nitrate (AgNO3) and stir with a magnetic stirrer for 30 min.

[0087] (3) Then, 0.5655 g of diammonium hydrogen citrate (C6H 14 O7N2), and stirred continuously for 30 min with a magnetic stirrer to fully mix them to obtain a precursor solution.

[0088] (4) The precursor solution was transferred to a 50 mL polytetrafluoroethylene reaction container and subjected to hydrothermal reaction at 100 °C for 24 h.

[0089] (5) After the reaction is completed, the mixture is naturally cooled to room temperature, the supernatant is removed, and the mixture is first centrifuged and washed three times with deionized water and then centrifuged and washed three times with anhydrous ethanol to obtain a precipitate A.

[0090] (6) The sample was then placed in a constant temperature vacuum drying oven at 70°C and dried for 24 h.

[0091] (7) The WO3 nanoparticles were then calcined in a muffle furnace at 450 °C for 120 min with a heating rate of 2 °C / min to obtain light yellow WO3 nanoflower powder.

[0092] like Figure 1 As shown in Figure 2, the phase structure of the sample was characterized by X-ray diffraction analysis (XRD). Figure 1 (a). It can be seen from the figure that all the diffraction peaks of WO3 and Ag@WO3 materials can correspond to the monoclinic WO3 phase (JCPDS No.72-0677) without other stray peaks, indicating that the prepared samples are of high purity. In addition, compared with the diffraction peaks of pure phase WO3, Ag@WO3 materials have almost similar diffraction peaks, indicating that the addition of Ag does not change the crystal structure of WO3. In addition, this diffraction peak with similar characteristics is mainly due to the trace amount of Ag in the composite material. However, careful observation shows that there is an obvious bulge in the diffraction peak near 35.8°. This is because the diffraction peak at 35.891° corresponds to the (004) crystal plane of hexagonal structure Ag (JCPDS No.41-1402), proving that Ag exists in the composite material. The functional groups of pure WO3 and Ag@WO3 composite materials were analyzed by Fourier transform infrared spectroscopy (FT-IR), as shown in the figure. Figure 1 (b) shows. It can be seen that the vibration peak near 734cm-1 can be attributed to the WO bond, which confirms the existence of WO3. The vibration peaks near 1652.53 and 3742.53cm-1 belong to the HOH bending mode and OH stretching mode, respectively, which may be due to the re-adsorption of water in the surrounding atmosphere. No vibration peak of Ag was observed in the FTIR spectrum, which may be due to too little Ag addition. Figure 1(c) shows the Raman spectra of WO3, WO3 and Ag@WO3. The spectral peaks of the Raman spectra at 200-500cm-1 and 700-850cm-1 belong to the bending vibration of δ(OWO) and the stretching vibration of υ(WOW) of WO3, respectively, indicating the presence of WO3 in the sample, which is consistent with the previous FTIR results. The Raman spectra of all samples show vibration bands near 263, 317, 712 and 805cm-1, proving that the sensitive material is a monoclinic phase, which is consistent with the XRD results. In addition, in monoclinic WO3 crystals, the band corresponding to the 712cm-1 mode is highly sensitive to changes in crystal symmetry and lattice distortion. Compared with the pure phase WO3, the peak intensity and broadening of this band have increased, indicating that the oxygen vacancy defects caused by lattice distortion have changed. In the Raman spectra of WO3 and Ag@WO3, the strongest Raman band observed near 805cm-1 can be attributed to the symmetric stretching vibration of the WO bond. In addition, through Figure 1 (d) From the locally enlarged Raman spectrum of 300-1500cm-1, it can be found that the Ag@WO3 material has an obvious bulge near 910cm-1. The peak here is caused by the doped Ag, which once again confirms that Ag is successfully doped into WO3. Figure 1 (eg) shows the ultraviolet photoelectron spectroscopy (UPS) test results of pure WO3 and Ag@WO3-7 nanoflowers. According to the calculation formula of formula 1, and its two tangent lines E on the x-axis cut-off-2 and E cut-off-1 The intercept of the two samples can be used to obtain the work function (W f ). Through measurement, we can know that the E cut-off-2 and E cut-off-1 They are 17.295, 17.685eV and 1.004, 1.112eV respectively. Therefore, the work functions of WO3 and Ag@WO3-7 are calculated to be 4.929eV and 4.647eV respectively. The results show that the work function of Ag-doped WO3 is smaller than that of WO3. The smaller the work function, the easier it is to lose electrons. In addition, due to the strong oxidizing property and electron affinity of oxygen, oxygen molecules will plunder electrons from semiconductor materials, causing Ag@WO3-7 to lose more electrons, forming a thicker electron depletion layer, and increasing the initial resistance value Ra of the Ag@WO3-7 sensor (which is different from the following Figure 5 c) The results are consistent), which significantly improves the gas sensing performance of the sensing material.

[0093] W f =hυ-(E cut-off-2 -E f )=21.22-(E cut-off-2 -E cut-off-1 ) (1)

[0094] Figure 2 In this paper, the band gap of semiconductor materials is analyzed using 310-950nm ultraviolet diffuse reflectance spectroscopy. Figure 2 (a) is the ultraviolet diffuse reflectance spectrum (UV-Vis) of WO3 and Ag@WO3-7. Figure 2 (b) shows the Tauc plots of WO3 and Ag@WO3-7 nanoflowers. The indirect band gap of the material is calculated by the extrapolation of formula (2) Figure 2 (b) Middle (αhv) 1 / 2 Calculated with the linear part of hv:

[0095] (αhv) 1 / 2 =A(hυ-Eg) (2)

[0096] Among them, α is the absorption coefficient, h is Planck's constant, υ is the frequency, A is a constant, and Eg is the semiconductor band gap width. The band gap energies of WO3 and Ag@WO3-7 samples are calculated to be 2.55eV and 2.34eV, respectively. After Ag doping, the band gap of WO3 becomes smaller, so it is easier to be activated by visible light with photon energy, promote electron migration, generate more oxygen vacancy defects, and show more excellent gas sensing performance.

[0097] X-ray photoelectron spectroscopy (XPS) was used to characterize the elemental composition and chemical valence state of the samples, such as Figure 2 (cf). Figure 2 (c) From the full XPS spectrum, we can see that the WO3 sample has three main peaks, namely W 4f, C 1s and O1s, with corresponding binding energies at 36.05, 284.02 and 530.09 eV, respectively. The Ag@WO3 sample has four main peaks, namely W 4f, C 1s, O 1s and Ag3d, which confirms that Ag is successfully doped into the WO3 material. C is used as a reference in the XPS experiment. Figure 2 (d) is the fine spectrum of W 4f. Two strong peaks are found at the binding energies of 7.10 eV and 34.98 eV in the pure WO3 sample, corresponding to W 4f 5 / 2 and W4f 7 / 2 W, indicating W +6 Compared with pure WO3, W 4f 5 / 2 and W4f 7 / 2 The binding energy peaks of Ag@WO3 material have obviously shifted to the positive direction, indicating that Ag doping has changed the chemical environment of WO3. Figure 2 (e) Ag 3d 3 / 2 and 3D 5 / 2They are mainly concentrated near the binding energies of 374.08eV and 368.08eV, with a fixed difference of 6eV between them, proving the existence of Ag in WO3 nanoflowers. Figure 2 (f) is the fine spectrum of O1s. Three peaks are fitted at the binding energies of 529.75 eV, 531.09 eV and 532.97 eV for WO3, representing the lattice oxygen (O L ), oxygen vacancies (O V ) and chemically adsorbed oxygen (O C Compared with pure WO3, the O1s peak of Ag@WO3 shifted negatively, and the oxygen vacancy (O V ) increases. In addition, through the calculation of their peak areas, it can be known that the lattice oxygen (O L ) and oxygen vacancies (O V ) accounts for as much as 95.57%, which is beneficial to the improvement of gas sensing performance. This is because, on the one hand, the increase of oxygen vacancies is conducive to increasing active sites. On the other hand, the lattice distortion caused by the introduction of Ag helps to optimize the electronic structure. The surface lattice oxygen (O L ) is more easily released and actively participates in the gas-sensitive reaction, which contributes to the high response value of the material. Therefore, compared with other samples, the Ag@WO3-7 gas sensor has the best gas-sensitive performance, which is consistent with the subsequent gas-sensitive test results.

[0098] Figure 3 In order to explore the microstructure of the samples, we performed scanning electron microscopy (SEM) characterization on WO3 and Ag@WO3. Figure 3 shown. Figure 3 (a) is the SEM image of WO3 nanoflowers. Figure 3 (be) shows the SEM images of WO3 nanoflowers with different Ag doping amounts. It can be clearly observed that all samples present a nanoflower structure self-assembled from nanosheets. After measurement, it can be known that the diameter of WO3 and Ag@WO3 spheres is about 2.3μm. With the increase of Ag doping amount, the size of the composite nanosheets becomes smaller and smaller, and the entire nanoflower surface becomes more and more fragmented, which may be due to the doping of Ag into the WO3 lattice. Figure 3 (fi) is the element composition image, in which W, O and Ag elements are evenly and densely distributed in the Ag@WO3 composite material.

[0099] Figure 4 In the study, the internal state and morphology of the samples were studied using a transmission electron microscope (TEM). The morphology of nanoflowers and nanoflower clusters can be seen from Figure 4 Observed in (a, c). By comparing the bright field and dark field images, it can be seen that the interior of the nanoflower is solid. Figure 4(b) is the HRTEM image of pure phase WO3, with lattice spacings of 0.377nm and 0.385nm corresponding to the (020) and (002) planes of monoclinic WO3, respectively. Figure 4 (d) is the HRTEM image of pure phase Ag@WO3. Compared with pure phase WO3, the lattice spacing is slightly increased. This is because Ag is added to the WO3 crystal and Ag replaces a small part of the W site, resulting in WO3 lattice distortion, which is conducive to the increase of oxygen vacancies and active adsorption sites.

[0100] Figure 5 In this study, a series of Ag-doped WO3 materials were assembled into gas sensors for the sensing characteristics of H2S gas at RT (25°C). First of all, the operating temperature will seriously affect the gas-sensing performance of the gas sensor, mainly because the working principle of the metal oxide semiconductor gas sensor is surface-controlled. In order to test the working temperature of WO3 and Ag@WO3 sensors, they were placed at 20-60 and 25-65°C respectively and exposed to 10ppm H2S gas atmosphere (such as Figure 5 (a and b)). It can be clearly seen that the response values ​​of all sensors show a "volcano-shaped" trend with the increase of temperature. This is because the increase of operating temperature can make H2S molecules obtain more energy to overcome the activation energy barrier and react with oxygen. However, if the temperature is too high, the gas molecules will move faster, and the accelerated reaction will also be accompanied by the desorption of gas molecules, so the response value will decrease. Among them, the best working temperature of WO3 is 40°C, and the response value is Ra / Rg=18.50. The Ag@WO3-5-11 sensor has the highest induction response value of H2S molecules at 35°C, and the response values ​​are 3468.10, 31863.23, 9624.17, and 23943.20 respectively. Among them, the response value of Ag@WO3-7 is the highest, which is about 1723 times that of pure WO3. Figure 5 (de) It can be seen that the response time of the Ag@WO3-7 sensor is only 5s at 35℃, but after 5 cycles of 10ppm H2S gas detection, it can be seen that the response value of the sensor is not particularly stable. In addition, compared with 35℃, the working temperature of 25℃ at room temperature can bring lower power consumption and avoid waste of resources. It is particularly important to note that even at room temperature (25℃), the response value of the Ag@WO3-7 sensor to 10ppm H2S gas is still as high as 11420, which is about 941 times that of the WO3 (Ra / Rg=12.14, RT) sensor at room temperature. Therefore, in the following tests, all our tests were performed at room temperature. Figure 5c is the curve of the sensor's resistance changing with the operating temperature. It can be clearly seen that the initial resistance value (Ra) of all sensors decreases with the increase of temperature, showing the typical characteristics of semiconductor materials. This can be attributed to the fact that higher temperature increases the energy of semiconductor material electrons, making it easier for electrons to cross from the conduction band to the valence band, and the carrier concentration increases sharply, thereby reducing resistance. More importantly, compared with pure WO3 ( Figure 5 (f)), the initial resistance value of the Ag@WO3 sensor is significantly higher, which will help to increase the response amplitude space of the sensor to show better gas sensing performance.

[0101] In addition, the response / recovery capabilities of WO3 and Ag@WO3 sensors to detect H2S gas were also investigated. Figure 6 As shown. The response time of WO3 sensor to 10ppm H2S gas at 40℃ is 30s. Compared with WO3, the response time of Ag@WO3-5, Ag@WO3-7, Ag@WO3-9 and Ag@WO3-11 sensors to 10ppm H2S at room temperature is significantly shortened, which are 8, 7, 7 and 10s respectively. More noteworthy is that with the increase of Ag doping amount, the gas sensitive response value increases, but when the doping amount of AgNO3 reaches 0.009g, the gas sensitive response decreases, indicating that the optimal AgNO3 doping amount of WO3 is 0.007g. The enhancement of Ag@WO3 gas sensitive response can be attributed to the electronic sensitization and chemical sensitization of Ag precious metal, which promotes the adsorption and dissociation process of O2 and H2S on the surface of the material and shortens the response time of the sensor. After the reaction is completed, it is transferred from the target gas to the air. Since Ag@WO3 has a weak ability to desorb H2S at low working temperatures and a long natural recovery time, a short pulse current needs to be provided outside the sensor to accelerate the separation of H2S gas molecules from the Ag@WO3 surface according to the Joule heating effect. At the beginning of the desorption process, the WO3 and Ag@WO3 sensors are heated at 80 and 200°C for 60s, respectively, and then the working temperature is lowered to the initial state. In subsequent tests, we used this method to achieve full recovery of H2S detection at low temperatures.

[0102] Continuous response dynamic cycle test is an important indicator to examine the gas sensing performance of the sensor. Figure 7 ad are the resistance change test curves of Ag@WO3-5, Ag@WO3-7, Ag@WO3-9, and Ag@WO3-11 facing the continuous change of 1-50-1ppm concentration of H2S gas. It can be clearly seen that all sensors can respond quickly and obviously once exposed to H2S gas, showing typical n-type semiconductor behavior, and as the H2S gas concentration increases, the response amplitude of the sensor also increases. Compared with pure WO3 ( Figure 8a), Ag@WO3 sensor has higher response value, faster response capability, and wider detection range. More noteworthy is that all sensors have almost the same response value corresponding to different concentrations of H2S gas in continuous response dynamic cycle test, indicating excellent short-term reproducibility. In addition, Figure 7 e further depicts the response concentration values ​​of each Ag@WO3 sensor to 1-50ppm H2S gas at room temperature. It can be seen that Ag@WO3-5, Ag@WO3-7, Ag@WO3-9 and Ag@WO3-11 sensors have obvious saturation sensitivity to high concentration H2S gas. More importantly, the response value of Ag@WO3 sensor is significantly higher than that of WO3 ( Figure 8 b), among which, the response value of the Ag@WO3-7 sensor is the largest and shows a certain linear relationship with the H2S gas concentration. Specifically, in the range of 1-10ppm H2S concentration, the linear fitting curve is y=897.17+1029.06x(R 2 =0.9931), in the range of 10-50ppm H2S concentration, the linear fitting curve is y=9581.58+152.36x(R 2 =0.9869). Figure 7 f is the detection limit test diagram of the Ag@WO3-7 sensor. The obvious response signal to low concentration H2S (10ppb, Ra / Rg=1.5) indicates that the sensor can detect trace H2S concentrations at the ppb level and has good stability (as shown in the inset: the test curve of the original data of 10ppb H2S detected three times in a row).

[0103] Fig. 9 In the field of gas sensing, the gas selectivity of the sensor is another key aspect in evaluating its practical application. Fig. 9 As shown in a, the responses of WO3 and Ag@WO3-7 sensors to different gases methanol, ethanol, ethylene glycol, NO2, CO, SO2 and H2S were tested, where the concentration of organic gas was 100ppm and the concentration of inorganic gas was 10ppm. The selection of these control gas groups took into account the main harmful gases present in industrial environments or the atmosphere, which may interfere with the detection of H2S. It can be clearly seen from the figure that the responses of WO3 and Ag@WO3-7 sensors to H2S gas are significantly high, and the response value of Ag@WO3-7 sensor is the highest, confirming its good selectivity. In addition, in order to discuss the effect of ambient humidity on the performance of gas sensors, we compared the response recovery curves of Ag@WO3-7 sensors to 10ppm H2S gas at ambient relative humidity of 20-68% ( Fig. 9bc). As the relative humidity of the environment increases, the response amplitude and initial resistance value of the sensor decrease. This is because the water molecules in the air compete with the H2S gas molecules for adsorption on the active sites on the surface of the material, thereby reducing the response value of the sensor. In addition, the water molecules in the air will also react with the oxygen ions adsorbed on the surface of the material to release electrons and return to the bulk of the material, thereby reducing the initial resistance value of the sensor. At the same time, we also tested the effect of the relative humidity change of the environment on the response value of the Ag@WO3-5, Ag@WO3-9 and Ag@WO3-11 sensors. Fig.10 As shown in Figure ac, all sensors show the same Ra and sensitivity decrease. Under different ambient humidity, the response value of Ag@WO3-7 sensor is still the best ( Fig.10 d). Fig. 9 d is the 10 consecutive repeatability tests of the Ag@WO3-7 sensor for 10ppm H2S gas at 25℃. It can be seen from the figure that the sensor has good repeatability and small fluctuations. In the 30-day long-term stability test of the Ag@WO3-7 sensor, the baseline of the sensor's response value tends to be stable, with a small downward trend, proving that it has good long-term stability, making them viable candidates for long-term detection of H2S. This slight decrease in response value may be due to the fact that H2S gas is not completely desorbed from the material after exposure to H2S gas, and partially forms substances such as WS2 and Ag2S.

[0104] Fig.11 In most MOS sensors, the gas sensing mechanism is usually explained by the adsorption-desorption model. Therefore, as a typical n-type MOS, the surface morphology of WO3 is closely related to its gas sensing performance. From the previous SEM and TEM results, it can be seen that the Ag@WO3 composite material is a nanoflower with good gas permeability. This special structure can provide more active sites and gas diffusion channels for gas adsorption. In order to better explain the sensing process, Fig.11 The electron depletion layer, electron transport and band structure changes of the sensor in air and H2S environments are shown.

[0105] When the material is placed in the air, due to the strong oxidizing property and electron affinity of oxygen, oxygen molecules will capture electrons in the material to form chemically adsorbed oxygen ions (O2 - , O - and O 2- In addition, Li et al. also proposed that the surface chemically adsorbed oxygen in the gas sensing process may come from the lattice oxygen of the oxide itself (O L), the previous XPS O1s analysis results and gas-sensing performance tests are consistent with this view. When Ag and WO3 are in contact with each other, because they have different Fermi levels and work functions, electrons will transfer from the conduction band of Ag to the contact interface until the Fermi levels are equal. Due to the downward band bending of WO3 and the interface barrier, the depletion region becomes thicker. Therefore, this electron sensitization effect will increase the Ra value. In addition, according to the previous UPS and UV-Vis results, Ag doping into WO3 crystals brings about lattice distortion, which reduces the work function and band gap of the material and increases the oxygen vacancy content, which is conducive to the formation of a thicker electron depletion layer, increases the initial resistance Ra of the material, and provides a wider space for the resistance change of the gas sensor. The test conditions of this study were carried out at room temperature, so the reaction of reaction formula 4 mainly occurred.

[0106]

[0107] O - (ads)+e - →O 2- (ads)(T>300℃) (6)

[0108] Since H2S has strong reducing properties, when the sensor is exposed to H2S gas, H2S molecules will react with the oxygen ions (O2 - ) reacts to generate SO2 and H2O, releasing electrons to return to the material body, thinning the depletion layer, thereby reducing the resistance of the material and obtaining a response signal (Equation 5). Since Ag has a chemical sensitization mechanism, it can increase the response signal and speed up the response. Specifically, on the one hand, Ag as a catalyst can activate H2S gas molecules and reduce the activation energy of H2S gas participating in the gas-sensitive reaction. On the other hand, Ag can also promote the adsorption of more oxygen molecules to form chemically adsorbed oxygen ions through the "overflow effect", and then overflow to form a high concentration of oxygen ions on the surface of the WO3 material. A large number of oxygen ions can react with more H2S gas, thereby significantly improving the gas-sensitive sensing performance.

[0109]

[0110] Due to the reverse overflow of oxygen ions, a small amount of Ag may be oxidized to Ag2O (reaction formula 8). Since the Gibbs free energy of reaction formula 9 is low, Ag2O will react with H2S to generate Ag2S with metallic properties, significantly reducing the resistance of the material. This is also the fundamental reason why the Ag@WO3 composite material has high selectivity for H2S gas.

[0111]

[0112] Ag2O+H2S→Ag2S+H2O (9)

[0113] In addition, in order to verify the gas sensing mechanism, the changes in the XPS O1s peak of the Ag@WO3-7 sensor before and after exposure to H2S gas were studied, such as Fig.12 shown. Fig.12 a) is the O 1s fine spectrum of the Ag@WO3-7 sensor in air. L ), oxygen vacancies (O V ) and chemically adsorbed oxygen (O C ) are located at 530.14, 530.50 and 532.63 eV, respectively, and the peak areas are 56.05%, 39.53% and 4.43%, respectively. When exposed to H2S gas, the lattice oxygen (O L ), oxygen vacancies (O V ) and chemically adsorbed oxygen (OC) both shifted negatively ( Fig.12 b)). More notably, the peak areas of Ag@WO3-7 O 1s after sulfurization also changed to 48.34%, 38.06% and 13.60%, respectively. L ) and oxygen vacancies (O V ) content decreased, which once again confirmed that the lattice oxygen (O L ) are also involved in the gas sensing process.

[0114] When the sensor is placed in the air after the reaction with H2S is completed, due to the strong bonding effect of Ag-S, the desorption rate of H2S from the material surface at room temperature is very slow. Therefore, a DC heating power supply is required to provide an additional heating voltage. According to the Joule heating effect, heating will accelerate the oxidation of Ag2S and promote the desorption of H2S gas from the material surface (reaction formula 10).

[0115] Ag2S+O2→Ag2O+H2S (10).

[0116] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.

Claims

1. A method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection, characterized in that: The steps of the method are: S1. Measure a certain amount of ethanol solution and pour it into a 100 mL beaker. Add a certain amount of WCl6 into the beaker and stir evenly with a magnetic stirrer to obtain a mixed solution A. S2, adding silver nitrate AgNO3 to the mixed solution A, stirring evenly with a magnetic stirrer to obtain a mixed solution B; S3, add diammonium hydrogen citrate C6H 14 O7N2, and continuously stirred with a magnetic stirrer to fully mix the mixture to obtain a precursor solution; S4, transferring the precursor solution into a 50 ml polytetrafluoroethylene reaction container and placing it in an oven for hydrothermal reaction; S5, after the reaction is completed and cooled naturally, centrifugation and washing with deionized water and anhydrous ethanol are performed to obtain a precipitate C; S6. Dry the precipitate C in a constant temperature vacuum drying oven for 6 to 10 hours, and then place it in a muffle furnace for calcination to obtain light yellow Ag-WO3 nanoflower powder.

2. The method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection according to claim 1, characterized in that: The magnetic stirring time of S1, S2 and S3 is 25 to 35 minutes.

3. The method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection according to claim 1, characterized in that: The oven temperature of S4 is 90-110° C., and the hydrothermal reaction time is 23-25 ​​h.

4. The method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection according to claim 1, characterized in that: The centrifugal speed of the S5 is 2000-4000 r / min, and the deionized water is centrifuged and washed 2-4 times, and the anhydrous ethanol is centrifuged and washed 2-4 times.

5. The method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection according to claim 1, characterized in that: The temperature of the constant temperature vacuum drying oven of S6 is 50-70°C, and the vacuum degree is maintained at 700-800Pa.

6. The method for preparing a three-dimensional multi-channel gas sensor for H2S gas detection according to claim 1, characterized in that: The muffle furnace calcination heating rate of S6 is 2°C / min, and the calcination time at 440-460°C is 110-130min.

Citation Information

Patent Citations

  • NO2 sensor based on precious metal Ag-supported mesoporous WO3 material and preparation method thereof

    CN105486724A

  • Preparation method of silver-phosphate-doped stannic oxide gas sensor gas sensitive material

    CN112067666A

  • Gas sensor for detecting H2S gas

    CN115753905A

  • Method for preparing tungsten trioxide precursor and hydrogen sulfide gas sensor fabricated using the same

    US20030099575A1

  • Flexible nitrogen dioxide gas sensor based on tungsten trioxide nanoparticles coated carbon nanotubes-graphene oxide hybrid and method for manufacturing the same

    US20170016867A1